PERBAIKAN SUSUT DAYA DAN JATUH TEGANGAN JARINGAN DISTRIBUSI 20KV PADA PENYULANG INTAKO PORONG SIDOARJO - Rohman, Deny Fatkhur; Wibawa, Unggul; Utomo, Teguh (Jurnal Mahasiswa TEUB, 2024)
Electrical energy is required for almost all activities in life, including government, industry, business and households. Therefore, it can be said that electricity is the mainstay of human life. People expect the availability of reliable and efficient electrical power for their daily lives. To meet this demand, a reliable and efficient electric power distribution system is required. However, creating a fully reliable and efficient distribution system in the field is really difficult. It can be said that power losses will definitely occur in the distribution system. PT PLN (Persero) as a supplier of electrical energy and the people or organizations that use it will certainly experience losses due to the power losses that occur. One of the most common methods of calculating power losses is to do it manually, but this method takes longer and produces less efficient results. ETAP (Electrical Transient and Analysis Program) is a technology and research advancement that accelerates and simplifies the calculation and simulation of power losses. Solutions that can be provided to reduce losses and voltage drops can be done by setting tap changers on substation transformers and also by increasing the capacity of overload transformers. This research includes the improvement of power losses and voltage drops in the 20 kV distribution system of Intako extension, PT PLN (Persero) ULP Porong. The method used is simulation with data obtained in the ETAP application. Based on the results of the load flow simulation in the existing conditions, there are 8 transformers that experience overload, namely PC415 (108.7%), PC18 (91.3%), PC82 (89.7%), PC122 (89.3%), PC194 (99.2%), PC533 (81.9%), PC589 (137%), PC671 (87%), and there are 3 buses that experience voltage drops that exceed the SPLN standards, while referring to the IEC standards, there are 24 buses that experience voltage drops that do not meet the standards. The total active power losses are 58.8 kW and the total reactive power losses are 285 kVAR. Conditions after adjusting the tap changer on the substation transformer by -2.5 on the primary side can reduce the voltage drop on several buses, but the transformer bus that is overloaded has not met the IEC standard of nominal voltage. Conditions after increasing the capacity of the transformer experiencing overload conditions can reduce the voltage drop value so that all buses meet the IEC standards of nominal voltage. The active power loss value decreased from 58.8 kW to 51.0 kW, and the reactive power loss value decreased from 285 kVAR to 273.2 kVAR. Keywords— Distribution System, Power Loss, Voltage Drop, Tap Changer, Up-Rating Capacity Transformer.